Eksistensi Faham Aliran De Stijl Pada Komposisi Fasade Bangunan Kolonial Belanda Dan Rumah Kontemporer - Hariyadi Salenda (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2013)
One of stream growing during of modern architecture is De Stijl stream. The stream of De Stijl (The Style) originated from the art of painting in the Netherlands founded in 1917 by the painter Theo van Doesburg and Piet Mondrian. In general, De Stijl proposed simplicity, abstraction, using a composition of horizontal-vertical lines, squares or rectangles, using a composition of red, yellow, blue, black, white, and gray, and use asymmetrical balance the composition. One of the buildings that are designed to follow the principles of De Stijl painting wing is Schroder House by Gerrit Rietveld. Because of Indonesia as the countries of the former Dutch colony with allegations that there are some colonial buildings of Dutch facade form more or less influenced by the ideas of De Stijl stream. Similarly, the development of buildings, contemporary homes in Indonesia. One sign that is legible facade form fields set by a combination square and rectangular-field side of the field lines forming in the vertical-horizontal, and combined with a horizontal flat roof forms. The most prominent existence from stream of De Stijl in architecture facade manifested in the Dutch colonial buildings and contemporary homes on the composition of the investigated area, the composition of line, texture and composition. However, the existence of De Stijl stream is the composition of the field tends to be manifested in facade buildings compared to the Dutch colonial building’s facade contemporary homes, as shown in the arrangement of areas which are arranged on the asymmetry facade balanced and use 2 forms a horizontal flat roof areas.